Financial Distress Ditinjau Dari Return on Asset, Debt to Asser Ratio, dan Current Ratio - Hasrina, Cut Delsie; Khairani, Ulfah; Azlim, Azlim (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2025)
This study aims to determine the effect of Return on Asset. Debt to Asset Ratio and Current Ratio on financial distress. The number of samples is 23. observations from 29 populations of property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. This study was conducted using a purposive sampling method. The data collection technique uses secondary data. Data. obtained from Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2022 using the Multiple Linear Regression method using SPSS. The results of this study indicate that Return on Asset (ROA) influences financial distress with a thinung value (107.445) greater than the table value (1.669) and a sig value of 0.000 <0.005. Debt to Asset Ratio (DAR) influences financial distress with a thuning value (31.978) greater than the tebe value (1.669) and a sig value of 0.000 < 0.005, while Current Ratio (CR) has no effect on financial distress with a tamang value (0.493) smaller than the table value (1.669) and a sig value of 0.623 > 0.005.